2014
DOI: 10.5303/jkas.2014.47.6.293
|View full text |Cite
|
Sign up to set email alerts
|

FIRST DETECTION OF 22 GHZ H2O MASERS IN TX CAMELOPARDALIS

Abstract: Simultaneous time monitoring observations of H 2 O 6 16 − 5 23 , SiO J = 1-0, 2-1, 3-2, and 29 SiO v = 0, J = 1-0 lines are carried out in the direction of the Mira variable star TX Cam with the Korean VLBI Network single dish radio telescopes. For the first time, the H 2 O maser emission from TX Cam is detected near the stellar velocity at five epochs from April 10, 2013 (φ = 3.13) to June 4, 2014 (φ = 3.89) including minimum optical phases. The intensities of H 2 O masers are very weak compared to SiO masers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The maser intensity ratios of J=2-1/J=1-0 and J=3-2/J=1-0 are known to have a large spread depending on individual stars and, for a single source, dependent on the stellar pulsation phase. The simultaneous monitoring results of SiO v=1, J=1-0, J=2-1, J=3-2 masers for the Mira variable, TX Cam showed that the average peak intensity ratios among SiO v=1, J=1-0, J=2-1 and J=3-2 masers were 0.85 for J=2-1/J=1-0 and 0.30 for J=3-2/J=1-0, although J=2-1/J=1-0 intensity ratios greater than 1 were also detected in some phases (Cho et al 2014). In addition, the maser line ratios for the Orich AGB, HaroChavira 20 were 1.33 for J=2-1/J=1-0 and 0.55 for J=3-2/J=1-0 during our observation (see Appendix B).…”
Section: Discussionmentioning
confidence: 95%
“…The maser intensity ratios of J=2-1/J=1-0 and J=3-2/J=1-0 are known to have a large spread depending on individual stars and, for a single source, dependent on the stellar pulsation phase. The simultaneous monitoring results of SiO v=1, J=1-0, J=2-1, J=3-2 masers for the Mira variable, TX Cam showed that the average peak intensity ratios among SiO v=1, J=1-0, J=2-1 and J=3-2 masers were 0.85 for J=2-1/J=1-0 and 0.30 for J=3-2/J=1-0, although J=2-1/J=1-0 intensity ratios greater than 1 were also detected in some phases (Cho et al 2014). In addition, the maser line ratios for the Orich AGB, HaroChavira 20 were 1.33 for J=2-1/J=1-0 and 0.55 for J=3-2/J=1-0 during our observation (see Appendix B).…”
Section: Discussionmentioning
confidence: 95%
“…The system noise temperatures of a single side-band range from 83 K to 241 K (at 22 GHz), from 132 K to 276 K (at 43 GHz), from 196 K to 395 K (at 86 GHz), and from 279 K to 573 K (at 129 GHz) depending on weather conditions and elevations. As a standard setting for our monitoring projects, such as the monitoring of TX Cam (Cho et al 2014), we used a digital spectrometer with the total band widths chosen from one 64 MHz mode for the H 2 O 6 16 − 5 23 line and three 64 MHz modes for the SiO v = 1, 2, and 29 SiO v = 0, J = 1-0 lines until the April 2012 observations. After that period, for the four bands (22, 43, 86, and 129 GHz), we used three 32 MHz modes for the H 2 O 6 16 − 5 23 , SiO v = 1, 2, J = 1-0 lines and two 64 MHz modes for the SiO v = 1, J = 2-1 and J = 3-2 lines.…”
Section: Observationsmentioning
confidence: 99%